A statistical quality control study on Acotex Industries Corporation - Arbis, Jenny; Borjal, Vera Adelle M.; Guanio, Terence Vittorio U.; Viniegra, Mia Karmina R. (Diliman, Quezon City College of Engineering, 2001)
This study is a statistical study on Acotex Industries Corporation. Acotex Industries Corporation specializes in high precision injection molding and provides a wide range of products from household goods to food packaging and semicon packaging. This study would only focus on the production of Klik-Reels due to its higher rejection rate as compared to other product lines. Klik-Reels are plastic reels used to house integrated circuits in tape form. These are primarily composed of high impact polystyrene and an additive of antistat. The reels are composed of two discs or flanges snapped together to hold the tape and facilitate its winding and unwinding. The flanges are produced by drying the raw materials, mixing them, and processing them in an injection molding machine. The company conducts in-process inspection, final inspection after packaging and a 48 hour test. Currently, Acotex monitors the measurements of the inner width and outer width between the flanges (W1 and W2), resistivity, and the occurence of visual defects (black spots, silver streaks and warpage). Based on the frequency of occurence of the defects, the group chose to focus on the three visual defects. Black spots are burn marks in the flanges. Silver streaks are visible white marks. Warpage is a distortion of the plastic material. Cause and effect diagrams were constructed to facilitate the problem analysis. Consultations with the process engineer and literature on injection molding processes helped the group identify the possible causes found in the material, mold and the machine. These causes were ranked according to the severity of the effects, probability of occurence and the probability of detection. These rankings were used in the Failure Mode Effects and Analysis (FMEA) from which risk priority numbers were obtained. These risk priority numbers would suggest which causes of the problems should be addressed first. From both the Cause and effect diagrams and the FMEA table, it was found that machine parameters are critical factors which contribute to the occurrence of the defects. Machine parameters include injection speed, nozzle temperature and cylinder temperature. Next on the priority list is the high moisture content of antistat. This is a possible cause of both black spots and silver streaks. Both of these causes however cannot be verified by the group due to the absence of specifications in the machine parameters and moisture levels. It is difficult to quantify how these causes actually contribute to the occurrence of the defects since there are no hard data available. The group constructed statistical control charts for the three defects using an attributes control chart. The group also constructed variable control charts for dimensional measurements. It was verified that the process is out of control. Also, the process capability is not sufficient to meet the specifications. The group therefore recommends a process of evaluation that the company could use in identifying the real causes of these quality problems and verifying them. The group recommends the implementation of Statistical Process Control. It was also suggested that the company also use Design of Experiments to determine the desirable moisture level of materials.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Acotex Industries Corporation; Package goods indstry; Food industry and trade; Quality control